The Relationship Between Family Functioning and Quality of Life in Patients With Gastric Cancer - Homa Poorabdolah; Nasrin Jafari Varjoshani; Masoumeh Namadian (Zanjan University of Medical Sciences and Health Services, 2022)
Background: Cancer can affect the quality of life of patients. Family support is essential in this disease. Objectives: This study aimed to determine the relationship between family functioning and quality of life in patients with gastric cancer. Methods: This cross-sectional study was performed on patients with gastric cancer at the Valiasr Medical Center in Zanjan, Iran, in 2018 using the census method. A specific standard questionnaire for the quality of life of cancer patients and a McMaster family assessment device were used to collect information. The descriptive analysis and Pearson's correlation coefficient were used to analyze data by SPSS software version16. Results: In total, 108 patients were assessed. The family functioning of the patients was assessed in the normal range and was partially good in all dimensions. The mean of general function (2.97 of 4) and affective responsiveness dimensions (2.31 of 4) was the weakest and the best, respectively. The overall quality of life, symptoms, and function [42.20 (2.65), 69.77 (7.23), 43.43 (7.38)] were at an unfavorable level. There was a significant inverse relationship (P<0.001) between the overall quality of life and the dimensions of family functioning: problem solving (r=-0.623), communication (r=-0.74), roles (r=-0.588), and behavior control (r=-0.718). A significant inverse relationship was also found between the overall quality of life and general family function (r=-0.577) (P<0.001). Conclusion: The study showed the association between quality of life and family function in patients with cancer. Improving family function in these patients using different methods is recommended.